Impossible stable peace in the Greek society: projects of koinè eiréne during the Corintian War - César FORNIS (Studia Historica: Historia Antigua, 2013)
The Corinthian War was closed in 386 B.C. by the first koinè eiréne, that prima facie promised to carry to the whole Greek world, if belligerent or not, a firm and everlasting peace. Six years before, with the war in progress and with Persia as arbiter and guarantor too, two essays or projects of «common peace» or «general peace» taken place, but failed because the imperialist concern of the involved states. In the present article we deal with the gestation, the interpretation of the clauses and the rasons, reals or supposed, of the breakdown of this new kind of juridical treaty that finally only was thoroughly accepted by the imposition of the hegemonic power, Sparta.